2012
DOI: 10.4103/1119-3077.104525
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion, antibiotics use, and surgery outcome in thyroid surgery: Experience from a suburban center in Nigeria

Abstract: Thyroidectomy is a safe surgery with minimal risk of complications. Grouping and cross-matching of blood in elective thyroidectomy is not an essential pre-operative preparation for all patients just as antibiotic therapy/prophylaxis made no difference in patient outcome. Simple multinodular goiter is the commonest histological diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…When it was soaked by 50 % the means that it contains about 25 ml of blood and if totally soaked; 100% this means that it contains 75 ml of blood [16]. Many researchers reported significant reduction of intra-operative blood loss by the use of ligasure system in total thyroidectomy when compared with the conventional sutureligation technique [6,17,18,19] and our data came in agreement with those reported results. The ligasure vessel sealing system can apply control, sealing vessels up to 7 mm in diameter and facilitates surgery by achieving the efficient haemostasis of blood vessels encountered during dissection, and allowing the rapid and secure division of vascularised tissues, while minimizing thermal injury to adjacent tissues [20].…”
Section: Discussionsupporting
confidence: 90%
“…When it was soaked by 50 % the means that it contains about 25 ml of blood and if totally soaked; 100% this means that it contains 75 ml of blood [16]. Many researchers reported significant reduction of intra-operative blood loss by the use of ligasure system in total thyroidectomy when compared with the conventional sutureligation technique [6,17,18,19] and our data came in agreement with those reported results. The ligasure vessel sealing system can apply control, sealing vessels up to 7 mm in diameter and facilitates surgery by achieving the efficient haemostasis of blood vessels encountered during dissection, and allowing the rapid and secure division of vascularised tissues, while minimizing thermal injury to adjacent tissues [20].…”
Section: Discussionsupporting
confidence: 90%
“…Those who were not having drain could be discharged at unnecessary which is in accord with another study 25 .…”
Section: Discussionsupporting
confidence: 71%
“…20 Many researchers reported a significant reduction of intraoperative blood loss by the use of suture less techniques in total thyroidectomy when compared with the conventional suture ligation technique and study data came in agreement with those reported results. [21][22][23] Al Juraibi et al also reported that the amount of intraoperative blood loss was 50-75 ml in sutureless group (mean 62.06±7.34) and 60-90 in the conventional group (mean 75.84±9.21). 24 Also, Noori et al reported in his study that the intraoperative blood loss measured by weighing the blood-soaked gauze and by calculating the intraoperative drain was also significantly less in the harmonic group than in conventional group (12±4 ml vs 28±9 ml, p<0.01).…”
Section: Discussionmentioning
confidence: 93%